2013
DOI: 10.1371/journal.pone.0068185
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Whitefly Transcriptional Responses to Beauveria bassiana Infection Reveals New Insights into Insect-Fungus Interactions

Abstract: BackgroundThe fungal pathogen, Beauveria bassiana, is an efficient biocontrol agent against a variety of agricultural pests. A thorough understanding of the basic principles of insect-fungus interactions may enable the genetic modification of Beauveria bassiana to enhance its virulence. However, the molecular mechanism of insect response to Beauveria bassiana infection is poorly understood, let alone the identification of fungal virulent factors involved in pathogenesis.Methodology/Principal FindingsHere, next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 83 publications
(121 reference statements)
3
28
2
Order By: Relevance
“…We also detected significant downregulation of cuticle proteins, which may be biologically important as Pandora penetrates the host cuticle. Similar to other transcriptomic studies of invertebrate responses to fungal infections (Xia et al 2013), we also found differential expression of genes that may be involved in detoxification, such as cytochrome P450 and peroxidasin, and in DNA repair, such as Cop 9 signalosome. A complete list of transcripts and expression values is included as a supplementary data file.…”
Section: Resultssupporting
confidence: 88%
“…We also detected significant downregulation of cuticle proteins, which may be biologically important as Pandora penetrates the host cuticle. Similar to other transcriptomic studies of invertebrate responses to fungal infections (Xia et al 2013), we also found differential expression of genes that may be involved in detoxification, such as cytochrome P450 and peroxidasin, and in DNA repair, such as Cop 9 signalosome. A complete list of transcripts and expression values is included as a supplementary data file.…”
Section: Resultssupporting
confidence: 88%
“…Recently, genetic sequencing technology has revealed the differential expression of hundreds of genes in B. tabaci in response to infection with the fungus Beauveria bassiana, as well as fungal genes differentially expressed at different stages of infection (Xia et al, 2013). The infection process is thus highly complex, and subject to specific host/pathogen evolutionary pathways.…”
Section: Discussionmentioning
confidence: 99%
“…61 On the other hand, a time-dependent induction of resistance genes is typically observed after 12 h. 14,24 This lag in the response is frequently due to the time needed for exogenous toxic molecules to penetrate the insect's cuticle. 62,63 Therefore, different CYPs could well act at different exposure times to protect various tissue-specific physiological pathways. Moreover, we also discovered that TcCYP4BN6 and TcCYP6BQ11 were both most highly expressed at the late pupae stage (Fig.…”
Section: Tccyp4bn6 and Tccyp6bq11 Were Regulated By Tclph To Be Respomentioning
confidence: 99%